The diary of C. L. Stretch - a critical edition and appraisal - Crankshaw, Grahame Bruce (Rhodes University, Faculty of Humanities, Department of History, 1960)
In the investigation of the Diary and its validity as evidence, the origin and structure of the treaty System, and the functioning of the treaties, in both their original form and subsequent modification, has been examined, with special reference to Stretch and the Gaika tribes.
Keywords: Stretch, Charles Lennox, 1797-1882; South Africa -- History -- Frontier Wars, 1811-1878; Treaties -- Interpretation and construction